Role of second transurethral resection in determining residual tumor in nonmuscle-invasive bladder cancer - Maskey, Pukar; Chalise, Pawan Raj; Sharma, Uttam Kumar; Gyawali, Prem Raj; Shrestha, Guna Kumar; Joshi, Bhola Raj (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Presence of residual tumors is not an uncommon event after transurethral resection of bladder tumor, and no studies from Nepal so far has addressed this issue. We conducted this study to determine the rate of residual tumors after first transurethral resection of nonmuscle-invasive bladder cancer, and to determine the factors associated with the presence of residual tumors and upstaging of nonmuscle-invasive bladder cancer.Methods: This was a prospective observational study of 43 patients of bladder cancer who had a diagnosis of nonmuscle-invasive bladder cancer following an initial transurethral resection. Demographic data and data on tumor characteristics were obtained. Patients underwent a second transurethral resection within 2 to 8 weeks. Histopathological findings at first and second resection were compared.Results: There were 20 patients with Ta tumor and 23 patiens with T1 tumor at initial resection. Residual tumor was detected in 18 (41.86%) patients overall, 2 in patients with Ta tumor (10%) and 16 in patients with T1 tumor (69.5%). Tumors with T1 stage, high grade, size more than 3 centimeters and sessile growth pattern were seen to have significant association with the presence of residual tumors. Six patients with T1 disease upstaged to T2 disease after second resection (26%), while there were no upstaging with Ta tumors. Tumors with T1 stage, sessile configuration and size more than 3 centimeters were found to be significantly associated with upstaging.Conclusion: A second transurethral resection for nonmuscle-invasive bladder cancer should be considered if the initial tumor is T1 stage, high grade, more than 3 centimeters in size and has sessile growth pattern.